Fabrication and tribological behavior of Al2O3/MoS2–BaSO4 laminated composites doped with in situ formed BaMoO4. (February 2018) - Song, Junjie; Hu, Litian; Qin, Baofeng; Fan, Hengzhong; Zhang, Yongsheng
Abstract: Three types of Al2 O3 /MoS2 –BaSO4 laminated composites doped with in situ formed BaMoO4 were prepared using a layer-by-layer method and spark-plasma-sintering. The friction properties and wear mechanisms of the composites at 25 °C–800 °C in continuous heating were studied. The combined actions of MoS2, BaSO4, BaMoO4 and tribochemical reaction products (MoO3 ) ensured the efficient formation of self-lubricating and tribo-induced films at different temperatures, thereby achieving continuous lubrication within a wide temperature range. The friction coefficient of the optimal laminated material coupled with Al2 O3 pin can be controlled in a low range (0.20–0.48), which is lower by approximately 0.24–0.44 times than that of monolithic alumina ceramics. Graphical abstract: High-performance alumina laminated composites are potential candidates for self-lubricating sealed bushings because of their excellent self-lubricating ability and mechanical properties. The aim of this study is to design and fabricate a new kind of alumina matrix laminated composites which could be used over a wide temperature range from approximately 25 °C up to as high as approximately 800 °C or even higher. Three types of Al2 O3 /MoS2 -BaSO4 laminated composites doped with in situ-formed BaMoO4 were prepared using a layer-by-layer method and spark-plasma sintering. The friction properties and wear mechanisms at 25 °C–800 °C in a continuous heating were studied. The compositions of the weak interfacial layers are the key factor affecting the tribological properties of the laminated composites. The combined action of MoS2, BaSO4 and BaMoO4 ensure the formation of lubricating films and tribo-induced films at different temperature, thus realizing the continuous lubrication within a wide temperature. Moreover, the tribochemical reaction products (MoO3 ) are also contributed to the reduction of friction resistance and abrasion of materials above 600 °C. The friction coefficient of the optimal laminated material coupled with Al2 O3 pin can be controlled in a low range (0.20–0.48), which was notably lower than that of monolithic alumina ceramics (0.84–1.10) in an elevated temperature environment (from 25 to 800 °C). Highlights: Al2 O3 /MoS2 -BaSO4 laminated composites doped with in situ-formed BaMoO4 were prepared. The friction properties and wear mechanisms at elevated temperature were evaluated. The properties were improved significantly by optimizing component of interface layer. The well-distributed lubricants promote the formation of effective lubricating films. The synergy of multi-lubricants realizes the continuous high-temperature lubrication.